2018
DOI: 10.1016/j.foodqual.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

European consumers’ interest in nutrition information on (sugar-free) chewing gum

Abstract: A B S T R A C TMuch consumer and public health research into nutrition labelling has explored the effects of information provision on consumer behaviour and how it can help consumers in making informed food choices. Among other things, it has been shown that European consumers' interest in and use of nutrition information varies greatly across country and product category. Chewing gum represents an understudied product category where little is known about whether consumers are interested in and would use nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
3
1
1
Order By: Relevance
“…This finding might relate to the fact that chewing gum is a product very likely perceived by consumers as scarcely affecting their diet and, thus, their health. In fact, consumers' interest in nutrition attributes related to chewing gum has been recently shown as relatively low (Hieke et al 2018). On the contrary, our results have shown that environmental concerns have a significant impact on participants' willingness to upgrade to the natural product.…”
Section: Discussioncontrasting
confidence: 55%
“…This finding might relate to the fact that chewing gum is a product very likely perceived by consumers as scarcely affecting their diet and, thus, their health. In fact, consumers' interest in nutrition attributes related to chewing gum has been recently shown as relatively low (Hieke et al 2018). On the contrary, our results have shown that environmental concerns have a significant impact on participants' willingness to upgrade to the natural product.…”
Section: Discussioncontrasting
confidence: 55%
“…Hartmann et al (2008) find no impact for NCs and HCs on consumers' perceptions of the food product, while Gineikiene et al (2017) present a negative perceived healthiness for yoghurts with HCs. Other aspects found in the literature to affect the perceived healthiness of food with NCs and HCs are the ingredients and their combination within the product carrier (Hieke et al, 2018;Menger-Ogle and Graham, 2018). More specifically, Cox et al (2011) and Landström et al (2009) demonstrate that consumers' perception of the healthiness of a food product with NCs and HCs is higher when the bioactive ingredient is 'naturally added' or inherent (Aschemann-Witzel and Grunert, 2017;Dean et al, 2007;Teratanavat and Hooker, 2006).…”
Section: Perceptionmentioning
confidence: 99%
“…Yet their ability to accurately interpret information diminishes with the increase in complexity [14]. Complex label designs also complicate consumers' understanding [15][16][17]. Further, [8] experimented and concluded that consumers focus on nutrition labels and make healthier purchases when the nutritional format is clear.…”
Section: Introductionmentioning
confidence: 99%
“…Culture also plays a significant role in food package label usage. For example, 3500 consumers from seven different European countries displayed significant differences in their preferences for sugar-free gum [16]. Consumers are more sensitive to product attribution, and thus focus on food types, price, and taste [24].…”
Section: Introductionmentioning
confidence: 99%